1994
DOI: 10.1159/000173865
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Impedance in the Assessment of Body Water Losses during Dialysis

Abstract: Multifrequency bioelectrical impedance was used to predict changes in body water compartments during renal dialysis. Weight loss during dialysis was assumed to be water loss. Predicted total body water (TBW) from impedance after dialysis did not differ significantly from TBW determined by deuterium oxide dilution. However, the predicted change in TBW from bioelectrical impedance largely exceeded the observed weight (water) loss. The predicted change in extracellular water was slightly but significantly lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…However, there are other indications in the literature that assessment of TBW may not be sufficiently accurate in conditions of change in hydration status and when body compartments are undergoing acute changes [26]. This may be because changes in the ratio of intra- to extra-cellular water, and of acute changes in these compartments, also influence resistivity [2629]. This may mean that there are fundamental problems with MF-BIA in assessing TBW and so in using MF-BIA in predicting hydration status.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other indications in the literature that assessment of TBW may not be sufficiently accurate in conditions of change in hydration status and when body compartments are undergoing acute changes [26]. This may be because changes in the ratio of intra- to extra-cellular water, and of acute changes in these compartments, also influence resistivity [2629]. This may mean that there are fundamental problems with MF-BIA in assessing TBW and so in using MF-BIA in predicting hydration status.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have validated the reliability of the measurement of total body water and intra‐ and extracellular water using the bioimpedance technique. It has been shown that multifrequency impedance is able to estimate adequately body water volume when compared with dilution methods.…”
Section: Methods For Assessing Venous Hemodynamics and Plasma Volumementioning
confidence: 99%
“…It consists of glucose and hydroxyethyl glucose that are interconnected by α‐glycosidic bonds. The use of HES as a dilution marker was first proposed in 1994. The HES method for plasma volume estimation has been found to be rapid, safe, well tolerated and acceptable for use in pregnant women, as it does not cross the placenta.…”
Section: Methods For Assessing Venous Hemodynamics and Plasma Volumementioning
confidence: 99%
“…Recent studies have shown the utility of multiplefrequency bioimpedance in the assessment of fluid state and its changes in patients with sepsis [14] and on maintenance HD [15,16].…”
Section: Introductionmentioning
confidence: 99%